Household well-being under sanctions: Insights from the Russian longitudinal monitoring survey - Sinikka Parviainen; William Pyle (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
This Policy Brief examines the economic well-being of Russian households in the wake of warrelated sanctions, leveraging ten years of data from the Russian Longitudinal Monitoring Survey (RLMS). Building on macroeconomic indicators suggesting resilience, we analyze subjective wellbeing, consumption patterns, and financial security across demographic and geographic groups. Our general findings point to increased satisfaction and savings, although we also find disparities. Ethnic Russians, for one, appear to be doing relatively well, whereas the opposite holds for retirement age citizens. The results offer insight into Russia's adaptability to sanctions and carry implications for political stability.
urn:nbn:fi-fe2025032120010
Keywords: 330; Russia; households; economy; sanctions; war